A CFD–DEM analysis of the de-cementation behavior of weakly cemented gas hydrate–bearing sediments in a hydrocyclone separator. (3rd October 2022) - Fang, Xing; Wang, Guorong; Zhong, Lin; Qiu, Shunzuo; Wang, Dangfei
Abstract: The de-cementation mechanism and performance of weakly cemented gas hydrate–bearing sediment (GHBS) particles in downhole hydrocyclone play a key role in the commercial production of natural gas hydrate through solid fluidization. This study considers the effect of weak cementation between particles in the hydrate separation process and studies the stress state of weakly cemented hydrates in the hydrocyclone flow field. A mechanical model and a maximum load calculation model of weakly cemented hydrate bond were established, providing a basis to judge the effect of the separator to break the cementation bond. Furthermore, the computational fluid dynamics (CFD) software and discrete element method (DEM) software were used to analyze the kinematic characteristics and the de-cementation process of weakly cemented particles occurring in the internal flow field and evaluate the hydrocyclone effects. According to the analysis and evaluation results, the cementation breaking effect of hydrocyclones is directly proportional to the inlet velocity in the range of 6–14 m/s and particle size in the range of 0.2–1.0 μm. This study provides certain theoretical support for the structural design of downhole hydrocyclones, the improvement of hydrate de-cementation performance, and the future commercial exploitation of natural gas hydrates (NGHs) in solid fluidization mining.